Secure protection for covid-19 infographic using blockchain and discrete cosine transform-singular value decomposition (DCT-SVD) watermarking - Muhammad Fajar Sidiq; Akbari Indra Basuki; Didi Rosiyadi; Iwan Setiawan; Yusnan Hasani Siregar; Sriyadi Sriyadi (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Covid-19 infographics have a crucial role in mitigating the covid-19 pandemic by conveying the complex Covid19 information in a form of a simple yet understandable image. However, keenly to contribute to mitigating Covid-19, numerous parties and agencies had released Covid-19 infographics that might contain incorrect or inaccurate information. To prevent such recurrent, this paper proposed an authentication system by using a blockchain-based authorization service that lets the authority guarantee the correctness and validity of the infographics in a transparent manner. We proposed smart contract-based watermarking requests and approval management that let anyone track the watermarking process. To prevent unauthorized infographic fabrications, we use the DCT-SVD method considering its robustness against various attacks. We deployed and evaluated the smart contract on Ethereum test networks (Ropsten, Rinkeby, Goerli, and Kovan) to compare the efficiency and the ease of use. The result showed that the test networks have similar efficiency while the Ropsten and Goerli have better ease of use. The watermark validation service is accessible via a web-based interface for anyone to check the validity of the infographic’s watermark.